Metaphor and metonymy in the digital age : theory and methods for building repositories of figurative language - Bolognesi, Marianna; Brdar, Mario; Despot, Kristina, 1978- (Metaphor in language, cognition, and communication,, 2019)
This book describes methods, risks, and challenges involved in the construction of metaphor and metonymy digital repositories. The first part of this volume showcases established and new projects around the world in which metaphors and metonymies are harvested and classified. The second part provides a series of cognitive linguistic studies focused on highlighting and discussing theoretical and methodological risks and challenges involved in building these digital resources. The volume is a result of an interdisciplinary collaboration between cognitive linguists, psychologists, and computational scientists supporting an overarching idea that metaphor and metonymy play a central role in human cognition, and that they are deeply entrenched in recurring patterns of bodily experience. Throughout the volume, a variety of methods are proposed to collect and analyze both conceptual metaphors and metonymies and their linguistic and visual expressions.